Effects of antioxidant Bis-carboxyethyl germanium sesquioxide added to bovine semen cryopreservation medium on in vitro assessed morphofunctional sperm parameters - Cruz, Tairini E. [UNESP]; Sitó-Silva, Luan [UNESP]; Filho, Rogério A. Almeida [UNESP]; Martins, Alicio [UNESP]; Marqui, Fernanda N. [UNESP]; Souza, Diego G.; Berton, Tatiana I. U.; Freita-Dell'Aqua, Camila P. [UNESP]; Oba, Eunice [UNESP] (Wiley, 2024)
This study investigated the impact of various Ge132 (Bis-carboxyethyl germanium sesquioxide) concentrations on frozen bovine semen. Ejaculates from three bulls were pooled and divided into six groups, each one with different Ge132 concentrations (0, 500, and 1000 μg/mL) and each group was incubated in different conditions (33°C for 30 min (D: D0, D500, and D1000), and the other was immediately cooled to 4°C (R: R0-control; R500 and R1000)). Thawed semen was evaluated for sperm characteristics by CASA and flow cytometer. Results showed better motility in the immediate cooling group without Ge132 compared with high Ge132 concentrations. Values for total motility dropped after 5 and 60 min in groups with high Ge132 levels and some control groups. Linearity increased with 1000 μg/mL Ge132, while straightness differed between moments in multiple groups. Membrane integrity was higher in a control group and certain Ge132 groups. Lower O2− generation occurred without Ge132. After oxidative stress induction, lipid peroxidation intensity increased with arachidonic acid, but D1000 had lower peroxidation than R0. Overall, Ge132 appears to have provided protection against PLM when subjected to oxidative stress, since even at high concentrations it maintained sperm metabolism.
Keywords: antioxidant; extender; reactive oxygen species; sperm quality